The BVI ISOPURE® 123 intraocular lens: a new hydrophobic preloaded extended monofocal IOL with intermediate vision correction - Ansari, Ejaz (Frontiers in Ophthalmology, 2024)
The BVI Isopure® intraocular lens (IOL) (PhysIOL, Liege, Belgium) is a fully refractive, aspherical, monofocal lens based on Isofocal technology. Isofocal technology provides cataract patients distance vision quality combined with improved unaided intermediate vision by accentuating the extended depth of field/focus (EDOF) effect whilst inducing minimal photic phenomena. METHODS: Pubmed, Web of Science, Scopus and Google Scholar searches were conducted for published research articles featuring the Isopure 123 IOL. RESULTS: Excellent uncorrected and corrected binocular distance visual acuity of at least 20/25 can be achieved; uncorrected binocular intermediate vision of 20/25 or better in 81% and 50% at 80 and 66 cm respectively, and 42% binocular near vision of 20/40 or better can be achieved. The defocus curve showed good visual acuity at far and intermediate distances with a depth of focus value of 1.50 D. Photic phenomena are minimal compared to other EDOF IOLs. Excellent contrast sensitivity was maintained compared to a standard monofocal IOL. CONCLUSION: Studies show that this isofocal optic design IOL provides excellent visual performance for far vision and functional intermediate vision with an increased range of vision with few photic phenomena. This lens is an effective option for providing functional intermediate vision and correcting aphakia.